Face-to-face versus remote and web 2.0 interventions for promoting physical activity. - Richards, J; Thorogood, M; Hillsdon, M; Foster, C (2013)
BACKGROUND: Face-to-face interventions for promoting physical activity (PA) are continuing to be popular as remote and web 2.0 approaches rapidly emerge, but we are unsure which approach is more effective at achieving long term sustained change. OBJECTIVES: To compare the effectiveness of face-to-face versus remote and web 2.0 interventions for PA promotion in community dwelling adults (aged 16 years and above). SEARCH METHODS: We searched CENTRAL, MEDLINE, EMBASE, CINAHL, and some other databases (from earliest dates available to October 2012). Reference lists of relevant articles were checked. No language restrictions were applied. SELECTION CRITERIA: Randomised trials that compared face-to-face versus remote and web 2.0 PA interventions for community dwelling adults. We included studies if they compared an intervention that was principally delivered face-to-face to an intervention that had principally remote and web 2.0 methods. To assess behavioural change over time, the included studies had a minimum of 12 months follow-up from the start of the intervention to the final results. We excluded studies that had more than a 20% loss to follow-up if they did not apply an intention-to-treat analysis. DATA COLLECTION AND ANALYSIS: At least two review authors independently assessed the quality of each study and extracted the data. Non-English language papers were reviewed with the assistance of an interpreter who was an epidemiologist. Study authors were contacted for additional information where necessary. Standardised mean differences (SMDs) and 95% confidence intervals (CIs) were calculated for continuous measures of cardio-respiratory fitness. MAIN RESULTS: One study recruiting 225 apparently healthy adults met the inclusion criteria. This study took place in a high-income country. From 27,299 hits, the full texts of 193 papers were retrieved for examination against the inclusion criteria. However, there was only one paper that met the inclusion criteria. This study reported the effect of a PA intervention on cardio-respiratory fitness. There were no reported data for PA, quality of life, or cost effectiveness. The difference between the remote and web 2.0 versus face-to-face arms was not significant (SMD -0.02; 95% CI -0.30 to 0.26; high quality evidence). The risk of bias in the included study was assessed as low, and there was no evidence of an increased risk of adverse events. AUTHORS' CONCLUSIONS: There is insufficient evidence to assess whether face-to-face interventions or remote and web 2.0 approaches are more effective at promoting PA.